2021
DOI: 10.1002/cptc.202100006
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Parameters Impacting the Photocatalytic Reduction of Carbon Dioxide in Ionic Liquids

Abstract: To overcome the chemical inertness of CO2, one strategy consists of pre‐activating or destabilizing it, to lower the reduction barrier, by preparing a carbene‐CO2 compound where the CO2 is bent rather than linear. This pre‐activation has been studied in ionic liquids (IL) based on imidazolium as a cation with different anions under conditions of mild pressure, room temperature and UV/Vis light. This screening showed that only 1‐butyl‐3‐methyl‐imidazolium acetate (C1C4ImOAc) was capable of effectively pre‐activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Peng an co-workers screened the influence of several co-solvents (H 2 O, iPrOH, and EM-(OH)Im•NTf 2 ) on the activation of CO 2 by Pd/g-C 3 N 4 catalyst in BMIm•OAc IL. [118] A high rate of CO (70.82 μmol g À 1 h À 1 ) with a selectivity of 100 % was found in iPrOH/BMIm•OAc reaction media. Recently, modified ZnSe quantum dots with thiol functionalized imidazoliumbased IL (3-(2-mercaptoethyl)-1-methyl-imidazolium tetrafluoroborate (MEMIm•BF 4 )) were prepared and generated up to 2.4 mmol CO g ZnSe À 1 in aqueous ascorbate solution.…”
Section: Photoreduction Of Co 2 By Ilsmentioning
confidence: 95%
See 1 more Smart Citation
“…Peng an co-workers screened the influence of several co-solvents (H 2 O, iPrOH, and EM-(OH)Im•NTf 2 ) on the activation of CO 2 by Pd/g-C 3 N 4 catalyst in BMIm•OAc IL. [118] A high rate of CO (70.82 μmol g À 1 h À 1 ) with a selectivity of 100 % was found in iPrOH/BMIm•OAc reaction media. Recently, modified ZnSe quantum dots with thiol functionalized imidazoliumbased IL (3-(2-mercaptoethyl)-1-methyl-imidazolium tetrafluoroborate (MEMIm•BF 4 )) were prepared and generated up to 2.4 mmol CO g ZnSe À 1 in aqueous ascorbate solution.…”
Section: Photoreduction Of Co 2 By Ilsmentioning
confidence: 95%
“…The authors concluded that the presence of citrazinate anion is the key factor that provided multiple sites for CO 2 absorption and acted as a photosensitizer. Peng an co‐workers screened the influence of several co‐solvents (H 2 O, iPrOH, and EM(OH)Im⋅NTf 2 ) on the activation of CO 2 by Pd/g‐C 3 N 4 catalyst in BMIm⋅OAc IL [118] . A high rate of CO (70.82 μmol g −1 h −1 ) with a selectivity of 100 % was found in iPrOH/BMIm⋅OAc reaction media.…”
Section: Photoreduction Of Co2 By Ilsmentioning
confidence: 99%